Respuesta :
Answer:
(6, 3)
Step-by-step explanation:
Step 1: Rearrange 2nd equation
2x = 2y + 6
x = y + 3
Step 2: Substitution
14(y + 3) - 2y = 78
14y + 42 - 2y = 78
12y + 42 = 78
12y = 36
y = 3
Step 3: Plug in y to find x
2x - 2(3) = 6
2x - 6 = 6
2x = 12
x = 6
Answer:
(6 , 3)
Solution,
[tex]14x - 2y = 78 \\ or \: 14x = 78 + 2y \\ x = \frac{78 + 2y}{14} ..........equation \: (i) \\ [/tex]
[tex] \\ \\ 2x - 2y = 6[/tex]
Putting the value of x from equation (i)
[tex]2 \times \frac{78 + 2y}{14} - 2y = 6 \\ or \: \frac{78 + 2y}{7} - 2y = 6 \\ or \: \frac{78 + 2y - 2y \times 7}{7} = 6 \\ or \: \frac{78 + 2y - 14y}{7} = 6 \\ or \: \frac{78 - 12y}{7} = 6 \\ or \: 78 - 12y = 6 \times 7 \\ or \: 78 - 12y = 42 \\ or \: - 12y = 42 - 78 \\ or \: - 12y = - 36 \\ or \: y = \frac{ - 36}{ - 12} \\ y = 3[/tex]
Now, putting the value of y in equation (i)
[tex]x = \frac{78 + 2y}{14} \\ = \frac{78 + 2 \times 3}{14} \\ = \frac{78 + 6}{14} \\ = \frac{84}{14} \\ = 6[/tex]
Value of X is 6
Value of y is 3
Learn more on:
https://brainly.com/question/15095311
hope this helps...
Good luck on your assignment...